Bacterial Wilt of Bananas in Libya: Isolation and Characterization of the Pathogen - ADAM, F. S.; NUESRY, S. M. (The Libyan Journal of Agriculture, 2023)
A bacterial disease of banana Musa chinensis cv. petit naine grown in a plastic house on a site west of Tripoli (Libya) was identified as banana wilt. The bacterium was isolated from parts of plants showing symptoms similar to that of Moko disease. Typical wilt symptoms were induced in young banana suckers following inoculation with the pathogen. Based on its cultural characteristics, biochemical and pathogenicity tests, the causal bacterium was identified as Pseudsomonas solanacearum, banana isolate biotype 2.